1995
DOI: 10.1007/bf00166597
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the intensity of male-driven evolution in rodents by using X-linked and Y-linked Ube 1 genes and pseudogenes

Abstract: Using sequence data from the last introns of ZFX and ZFY genes, we previously estimated the male-to-female ratio (alpha) of mutation rate to be close to 6 in higher primates and 1.8 in rodents. As the mutation rate may vary among different regions of the mammalian genome, it is interesting to see whether sequence data from other regions will give similar estimates. In this study, we have determined the partial genomic sequences of the ubiquitin-activating enzyme E1 genes (Ube 1x and Ube 1y for the X-linked and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Most studies of male-biased mutation so far reported using the evolutionary approach have analysed either mammals (Shimmin et al 1993a(Shimmin et al , 1994Chang et al 1994;Chang & Li 1995;Agulnik et al 1997;Huang et al 1997;McVean & Hurst 1997;Bohossian et al 2000;Lawson & Hewitt 2002;Malcom et al 2003;Tucker et al 2003;Sandstedt & Tucker 2005) or birds (Ellegren & Fridolfsson 1997;Kahn & Quinn 1999;Carmichael et al 2000;Garcia-Moreno & Mindell 2000;Bartosch-Härlid et al 2003;Axelsson et al 2004;Berlin et al 2006), so the correlates with life history are mainly restricted to these groups of species. A study of salmonid fishes revealed an a m estimate of 6 (Ellegren & Fridolfsson 2003) and in dioecious plants there are also evidence for higher rate of mutation on the Y than the X chromosome (Filatov & Charlesworth 2002;Whittle & Johnston 2002); indeed, there are more cell divisions in pollen than in ovule production.…”
Section: Life History and The Male Mutation Biasmentioning
confidence: 99%
“…Most studies of male-biased mutation so far reported using the evolutionary approach have analysed either mammals (Shimmin et al 1993a(Shimmin et al , 1994Chang et al 1994;Chang & Li 1995;Agulnik et al 1997;Huang et al 1997;McVean & Hurst 1997;Bohossian et al 2000;Lawson & Hewitt 2002;Malcom et al 2003;Tucker et al 2003;Sandstedt & Tucker 2005) or birds (Ellegren & Fridolfsson 1997;Kahn & Quinn 1999;Carmichael et al 2000;Garcia-Moreno & Mindell 2000;Bartosch-Härlid et al 2003;Axelsson et al 2004;Berlin et al 2006), so the correlates with life history are mainly restricted to these groups of species. A study of salmonid fishes revealed an a m estimate of 6 (Ellegren & Fridolfsson 2003) and in dioecious plants there are also evidence for higher rate of mutation on the Y than the X chromosome (Filatov & Charlesworth 2002;Whittle & Johnston 2002); indeed, there are more cell divisions in pollen than in ovule production.…”
Section: Life History and The Male Mutation Biasmentioning
confidence: 99%
“…Spontaneous mutation rate traditionally was measured in mutation accumulation experiments which are tedious and, for practical reasons, have been done mainly on viruses and a few rapidly replicating bacterial species [241, 242]. Dating the origin of pseudogenes and then comparing their divergence against their functional counterparts [243-246] allow for an estimation of spontaneous mutation rate (approximated by the neutral substitution rate) and mutation spectrum. High mutation rate and large population size increase the chance of parasites developing drug resistance.…”
Section: Bioinformatics and Drug Resistancementioning
confidence: 99%